(untitled) (Revista Internacional de Formação de Professores, 2016)
The main aim of this work is to address the role of experiential knowledge in building professional teaching knowledge and reflect on their epistemological and teachers training implications. It is argued on the need to implement a practice of initial training of teachers to enable the future professionals for professional autonomous and active performance. But also, understand that they only have started a process of learning and building the professional component that will continue and renew throughout their professional career.